Copper(II)/Palladium(II) catalysed highly selective cross-coupling of terminal alkynes in supercritical carbon dioxide. Issue 15 (12th April 2018) - Wang, Yunlong; Suo, Quanling; Han, Limin; Guo, Linlin; Wang, Yaqi; Li, Fawang
Abstract: An efficient protocol for the synthesis of unsymmetrical 1, 3-diynes was developed using supercritical carbon dioxide (ScCO2 ) as the solvent. The direct coupling of two different terminal alkynes is catalysed by a bimetallic catalyst, CuCl2 ·2H2 O/Pd(NH3 )4 Cl2 ·H2 O, in the presence of the base tetramethylethylenediamine (TMEDA) and O2 . In pure ScCO2, our bimetallic catalytic system maintains high activity over a wide substrate scope to provide unsymmetrical 1, 3-diynes in good to excellent yields. In the proposed reaction mechanism, the synergistic cooperation between copper(II) and palladium(II) centres is responsible for the superior selectivity of the cross-coupling. Graphical abstract: